A NEW APPROACH TO THE TREATMENT AND PREVENTION OF SYPHILITIS INFECTION - Ravshanova D.T. (PEDAGOGS, 2024)
Annotation: in this article, an attempt was made to reveal the main reasons for the development of a method for indicating molecular markers of organ lesions in syphilitic infection based on the chromato-mass spectrometric analysis of biological fluids and tissues of the body of a patient with syphilis. To carry out scientific work, the author conducted a study of biological material (blood, cerebrospinal fluid, urine) obtained from 152 patients with syphilis aged 15 to 60 years (men 45.5 women - 55.5%) using GC-MS analysis methods. The problem in question is still little studied, therefore, requires more thorough research.